ELAKSANAAN FUNGSI DPRD DALAM MENGATUR MEKANISME PEMILIHAN KEPALA DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Martina Male (KEADILAN PROGRESIF, 2019)
The system of government in Indonesia according to the 1945 Constitution, based on theexplanation stated that the regions of Indonesia are divided into provincial and provincial regionswill also be divided into smaller areas in autonomous regions. In legal politics, the most essential inthe implementation of autonomous regional government is the granting of the broadest authority tothe regions accompanied by the granting of certain rights and obligations. In the reality in the field,this policy was not implemented in accordance with the provisions of the Act. The lack of optimalpublic services in serving the people in several regions in Indonesia in various fields, includinggovernment agencies, has not yet been able to provide maximum public services, so in this paper willdiscuss how the efforts made by the Regional Government, especially in Gedong Tataan Subdistrict,Pesawaran District in organizing and improving public services based on its Regional AutonomyPrinciple. The efforts made in the discussion and solving problems in this study were carried outusing a juridical / normative approach and empirical approach. The implementation of public policybased on the principle of regional autonomy in the District of Pesawaran District Gedong Tataan isin accordance with Law Number 23 of 2014 concerning Regional Government and Law Number 25 of2009 concerning Public Services, but there are technical obstacles such as the distance from publicservices to one another, less responsive, less informative and lacking coordination in service delivery.Efforts that can be made by the Gedong Tataan District Government in improving the quality ofpublic services are through revitalization, restructuring and deregulation in the field of publicservices. Suggestions that can be given to the Regional Government, especially in the District ofPesawaran District Gedong Tataan in carrying out public services based on the principle ofautonomy are: expected in carrying out the process of implementing public services must be inaccordance with Law Number 25 of 2009 concerning Public Services and expected improvement inthe quality of behavior and professionalism of the apparatus government, creating public servicepolicies that are not too procedural and convoluted, and improve facilities that support qualityservices.